Aerococcus-Related Infections and their Significance: A 9-Year Retrospective Study - Sahu, Kamal Kant (J Microsc Ultrastruct, 2020)
INTRODUCTION: Aerococcus spp. is a Gram-positive, catalase- and oxidase-negative, microaerophilic, nonmotile bacteria species rarely associated with human infections such as arthritis, bacteremia, endocarditis, and meningitis. The bacteria are also often confused with streptococci species or treated as a contaminant. PATIENTS AND METHODOLOGY: We conducted a retrospective, observational cohort study on all patients with Aerococcus spp. isolates in blood samples from July 2010 to June 2019. All categorical data were presented as counts and proportions, whereas continuous data were presented as median and interquartile ranges. RESULTS: A total of 20 Aerococcus spp. isolates were identified over the study period of 9 years. Of these, Aerococcus urinae was isolated in 10 (50%), Aerococcus viridans in 6 (30%), and Aerococcus spp. (not speciated) in 4 (20%). The median age was 74.3 years (12 males and 8 females). The two most frequent presentations were fever (15 of 20) and altered mentation (6 of 15). Most of the patients (11 of 15) had at least one predisposing comorbidity related to the urinary tract system (8 with recurrent urinary tract infection, 7 with urinary incontinence, 3 with an indwelling catheter, 2 with renal stones, and 1 each with benign prostatic hyperplasia and a recent cystoscopy). The median white blood cell count was 18,426 cells/mL, median hemoglobin 10.96 g/dL, median platelet count 191,000 cells/μL, median blood urea nitrogen 28.6 mg/dL, and median creatinine 1.54 mg/dL. The urinary tract was the most likely source of bacteremia (10 of 20) based on either imaging findings (5 cases), positive urine culture for Aerococcus spp. (4 cases), or instrumentation history (1 case). In the rest, the cause of bacteremia could not be found. Endocarditis was suspected in 9 out of 20 patients. Transthoracic echocardiography/transesophageal echocardiography (TEE) confirmed 3 cases (2 aortic valves, 1 mitral valve and pacemaker). Interestingly, one case had septic emboli causing a right frontal stroke with a normal TEE and normal Doppler study for deep venous thrombosis. Blood cultures were positive in 35% (7 of 20) with polymicrobial growth, 3 with coagulase-negative staphylococci, 2 with Enterococcus faecalis, and the other 2 each with Diphtheroids spp. and Proteus mirabilis. Of the 20 cases, 9 and 10 required intensive care unit level care and vasopressor support, respectively. Most of the patients were treated for 5–14 days except the 3 cases with infective endocarditis (IE). The median hospital stay duration was 6.55 days with 2 fatalities (2 out of 20 patients). CONCLUSION: Old age and underlying urologic conditions are the best-known risk factors for Aerococcus spp. infection. Recent advances in diagnostic technology have led to an increase in detection of Aerococcus spp.-related infections. The rare occurrence of Aerococcus spp. in human infections and resultant lack of randomized control trials have resulted in a significant degree of clinical uncertainty in the management of Aerococcus spp. IE.